South Asian history and scandal in the Archive: Hindu law. Issue 1 (2nd January 2016) - Washbrook, David
ABSTRACT: Scanning the South Asia Archive, it is hard not to be impressed by the rich possibilities of investigation and discovery. Part of the Archive deals with how India's British rulers attempted to govern, and thus to shape, its society through the passage towards modernity. These days we are rightly suspicious that their interests lay more in their own modernity than that of their colonial 'subjects' and that their rule was marked more by authoritarianism and exploitation than responsibility and compassion – and many documents in the Archive, especially concerning taxation and criminality, certainly attest the case. The reports and commissions on various acts of riot and revolt are frequently marked by a bizarre combination of bravado and anxiety. Equally, they – and many other policy documents in the Archive – reveal often deep-seated differences of opinion within the establishment. Policy documents and reports of colonial officials, however, constitute only one part of the Archive. Much more, it provides evidence of how Indians tried to make, and remake, their own society during this period. Many of the 'non-official' sources contained in the Archive help to fill out a much broader picture of what it was like to live in this society at this time, and how Indians built their own world according to their own ideas and actions.